Impact response of shear thickening fluid filled polyurethane foam core sandwich composites. (1st July 2020) - Caglayan, Cigdem; Osken, Ipek; Ataalp, Altug; Turkmen, Halit S.; Cebeci, Hulya
Abstract: Up to date, a considerable experimental work has been performed to reveal the impact behavior of polymer foam core sandwich composites. Though, a few attempts have been made to integrate shear thickening fluids (STF) in closed cell rigid polyurethane foams (PU). STF possess a unique rheological property providing a rapid response to the structure against impact loads. The effects of STF on polymer foam cell morphology, thermal stability, and mechanical performance are investigated with advanced characterization techniques. The drop-weight impact test results of sandwich composites show that STF filled PU foam cores exhibit a higher energy absorption rate compared to its neat counterpart. Specific compressive strength and impact energy absorbing capability of STF filled PU foam cores increase with respect to the higher cell thickness-to-length ratios and higher cell densities achieved with STF inclusion. In addition, STF filled PU foam core sandwich composites are found to respond with lower damage width compared to neat PU foams.